In search of factors related to migration affecting children's health - an analysis of documents guiding health visits within the Swedish school health services - Emmie Wahlström; Marie Golsäter; Inger K. Holmström; Peter Larm; Maria Harder (BMC, 2023)
Abstract Background Migration affects the health of children worldwide. Therefore, school nurses who encounter these children as part of their everyday practice need support from guidelines on how to promote the health of children who have migrated or whose parents have migrated. Yet knowledge regarding such content in guidelines of school nursing practice is sparse. Therefore, this study aims to investigate how municipal and regional guidelines and health questionnaires used in health visits in the Swedish school health services include factors related to migration that affect children's health. Methods A document analysis of municipal and regional guidelines and health questionnaires guiding school nurses' practice in health visits was conducted during the autumn of 2020. In total, 687 guidelines and health questionnaires were analyzed using deductive content analysis. Results The results show that municipal and regional guidelines and health questionnaires used in health visits in the Swedish school health services include content on many factors related to migration that affect children's health. Yet the content was limited, and none was found on factors related to discrimination based on ethnicity or origin. Conclusion Guidance related to promoting the health of children who have migrated or whose parents have migrated should include all factors affecting these children's health. Therefore, to strengthen school nurses' evidence-based practice, guideline development might be needed, although guidelines and health questionnaires exist and include content on many factors related to migration affecting the health of children in order to provide equitable healthcare for all children, regardless of country of origin.